Pronunciation errors of Arabic consonants among chinese students in Gansu, China - Yalan, Ma (2020)
This thesis illustrates the similarities and differences between Arabic and Chinese phonetic systems by comparing its phonetic systems. This research mainly focuses on two research questions: (1) What errors were made by Chinese students (in Northwest Normal University first-grade to fourth-grade) in pronunciation of Arabic consonants that do not exist in Chinese? (2) What are the factors of the Arabic pronunciation errors on letters made by the Northwest Normal University students of first-grade to fourth-grade? Correspondingly, the researchers selected Northwest Normal University students as the research samples, and used qualitative research methods to conduct descriptive analysis to achieve the following two research objectives: (1) To identify Chinese students’ pronunciation errors in Arabic consonants that do not exist in Chinese. (2) To describe the factors of errors made by the Northwest Normal University students of first-grade to fourth-grade. Namely, to investigate the consonant pronunciation errors of Chinese students in the process of Arabic phonetic learning, and use interviews to find the reasons for these students' mistakes. Through research, we found that Chinese students are prone to make consonants, for example, it is easy to pronounce ه / h / as h / x / or ح / ħ /. The researcher hopes to improve Chinese students' comprehensive understanding of Arabic phonetic learning and avoid the same errors in the process of learning consonants.